Effect of Dietary Supplementation of Arjuna (Terminalia arjuna) Bark and Sahjan (Moringa oleifera) Leaf Powder on the Egg Quality and Egg Composition of Uttara Chicken - Sharma, A.; Kumar, A.; Sharma, R. K.; Singh, B.; Mondal, B. C.; Prakash, O.; Gangwar, S.; Sarma, G. (International Journal of Bio-resource and Stress Management, 2024)
This study was conducted during February, 2022 to February, 2023 to evaluate effect of dietary supplementation of Terminalia arjuna bark and Moringa oleifera leaf powder on external and internal egg quality parameters and egg composition of Uttara chicken. Day old chicks (n=72) were distributed into six treatment groups, having three replicates of 4 birds each. Birds were fed T0 (control diet), T1 (Basal diet+1% Arjuna bark powder+1% Sahjan leaf powder), T2 (Basal diet+1% Arjuna+2% Sahjan), T3 (Basal diet+1% Arjuna+3% Sahjan), T4 (Basal diet+1% Arjuna+4% Sahjan) and T5 (Basal diet+1% Arjuna+5% Sahjan). Eggs from the T3 group consistently exhibited higher (p<0.01) egg weight, thicker egg shell, greater egg shell weight, and improved albumen quality, as evidenced by higher albumen height, albumen index, and Haugh unit values. Yolk weight and yolk color score were also improved (p<0.01) in treatment groups, notably T2 and T3 as compared to control group. The eggs from the T3 group had significantly higher (p<0.05) crude protein content and lower yolk cholesterol levels compared to other groups. There was no significant difference in moisture (%) and ether extract (%) content of egg. Thus, it may be concluded that Arjuna bark @ 1% and Sahjan leaf @ 3% powder have positively influenced egg quality and egg composition of Uttara chicken indicating its potential as a beneficial dietary supplement in poultry diet.